Bilayered negative-pressure wound therapy preventing leg incision morbidity in coronary artery bypass graft patients: A randomized controlled trial. Issue 3 (January 2017) - Yu, Yongchao; Song, Zhigang; Xu, Zhiyun; Ye, Xiaofei; Xue, Chunyu; Li, Junhui; Bi, Hongda
Abstract: Backgrounds: The harvesting of great saphenous veins for coronary artery bypass graft (CABG) patients may result in significant complications, including lymphorrhagia, lymphoedema, incision infection, wound dehiscence, and skin flap necrosis. We investigated the function of a self-designed bilayered negative pressure wound therapy (b-NPWT) for reducing the above-mentioned complications using a clinical randomized controlled trial. Methods: A single-center, pilot randomized controlled trial was conducted. From December 2013 to March 2014, a total of 72 coronary heart disease patients (48 men and 24 women) received CABG therapy, with great saphenous veins were selected as grafts. Patients were equally randomized into a treatment and a control group. After the harvesting of the great saphenous veins and direct closure of the wound with sutures, b-NPWT was used for the thigh incision in the treatment group for 5 days (treatment thigh). Traditional surgical pads were applied to both the shank incisions of the treatment group patients (treatment shank) and the entire incisions of the control group (control thigh, control shank). Postoperative complications were recorded and statistically analyzed based on outcomes of thigh treatment, shank treatment, thigh control, and shank control groups. Results: The incidence rates of early complications, such as lymphorrhagia, lymphoedema, infection, wound dehiscence, and skin flap necrosis, of the vascular donor site in the thigh treatment group was significantly lower than those in the 3 other groups. Conclusions: The self-designed b-NPWT can effectively reduce postoperative complications, such as lymphedema, incision infection, wound dehiscence, and skin flap necrosis, in CABG patients who underwent great saphenous veins harvesting. Trial registration: ClinicalTrials.gov. The unique registration number is NCT02010996.